Psychotherapies for Adolescents with Subclinical and Borderline Personality Disorder: A Systematic Review and Meta-Analysis. (January 2020) - Wong, Jennifer; Bahji, Anees; Khalid-Khan, Sarosh
Background: Evidence regarding the efficacy of psychotherapy in adolescents with borderline personality disorder (BPD) symptomatology has not been previously synthesized. Objective: To conduct a systematic review and meta-analysis of the randomized controlled trials (RCTs) in order to assess the efficacy of psychotherapies in adolescents with BPD symptomatology. Methods: Seven electronic databases were systematically searched using the search terms BPD, adolescent, and psychotherapy from database inception to July 2019. Titles/abstracts and full-texts were screened by one reviewer; discrepancies were resolved via consensus. We extracted data on BPD symptomatology, including BPD symptoms, suicide attempts, nonsuicidal self-injury, general psychopathology, functional recovery, and treatment retention. Data were pooled using random-effects models. Results: Of 536 papers, seven trials (643 participants) were eligible. Psychotherapy led to significant short-term improvements in BPD symptomatology posttreatment ( g = −0.89 [−1.75, −0.02]) but not in follow-up ( g = 0.06 [−0.26, 0.39]). There was no significant difference in treatment retention between the experimental and control groups overall (odds ratio [ OR ] 1.02, 95% confidence interval [CI], 0.92 to 1.12, I 2 = 52%). Psychotherapy reduced the frequency of nonsuicidal self-injury ( OR = 0.34, 95% CI, 0.16 to 0.74) but not suicide attempts ( OR = 1.03, 95% CI, 0.46 to 2.30). Conclusions: There is a growing variety of psychotherapeutic interventions for adolescents with BPD symptomatology that appears feasible and effective in the short term, but efficacy is not retained in follow-up—particularly for frequency of suicide attempts.